BENEFITS OF RECREATIONAL SWIMMING ON THE QUALITY OF LIFE OF CHILDREN AND ADOLESCENTS WITH AUTISM SPECTRUM DISORDER: A NARRATIVE REVIEW - Delfino, Michele Fernanda Rosa; de Oliveira, Dílmerson; Morais, Gleison Silva; Pedrosa, Rayane Eduarda de Paula; dos Santos, Natália Luiza; Dutra, Selmiléia Franciane de Andrade; Rosa, Eneder Donizete; Bedim, Natiele Resende (Seven Editora, 2025)
The main findings show original articles which found in their outcomes that the practice of recreational and adapted swimming between 6 and 16 weeks, between 1 and 5 times a week, and lasting 45 to 60 minutes, was able to cause an improvement in cognitive and emotional development, with a reduction in irritability, improvement in motor and physical aspects, especially body balance, respiratory muscle strength, sleep quality and a reduction in inflammatory markers, as well as an improvement in socialization and social interaction in children and adolescents with ASD. Therefore, it can be concluded that the practice of aquatic activities based on swimming can improve and stimulate the cognitive, motor, physical, emotional and social development of children and adolescents with ASD.DOI: https://doi.org/10.56238/sevened2025.021-027